Do beverage workers in Enugu state Nigeria comply with health safety measures? A cross sectional study of two breweries - Ezeoke, Uche Enuma; Mamah, John Basco Emmanual; Ndu, Anne Chigedu; Mbachu, Chinyere Ojiugo; Okeke, Chinyere Cecilia; Kate, Umeobieri Ancilla (International Journal Of Community Medicine And Public Health, 2020)
Background: Some workplace accidents happen because workers fail to do their work in the safest possible way. Human beings have an innate desire to be safe, and their commitment to maintaining safe work environment is imperative for occupational health. However, employees’ contributions to workplace accident and injury is underexplored. Methods: Cross-sectional quantitative study was undertaken in two beverage industries in Enugu state. In order to observe a proportion of 50% in staff compliance to safety measures with precision of 5% and confidence level of 95%, 217 full-time employees were selected from each industry. Stratified sampling technique was used to select respondents across 5 units/departments. Data was collected using pre-tested structured questionnaire and analyzed using descriptive statistics. Statistical significance was set at p<0.05. Results: Use of any form of safety device was reportedly high among respondents, 413 (97.4%). However, only 278 (67.3%) reported using them on a daily basis. Aprons 103 (24.9%), helmets 163 (39.5%), and hand gloves 197 (47.4%) were the least commonly used safety devices. The only reason reported for inconsistent use of safety devices was discomfort. Consistent use of safety devices correlates significantly with demographic characteristics such as age, sex, level of education, length of years of work and unit/department (p<0.001), as well as previous history of workplace injury (p=0.01). Conclusions: Consistent compliance with safety measures among factory workers is suboptimal and correlates significantly with demographic characteristics and previous history of workplace injury.